Male circumcision and women's risk of incident chlamydial, gonococcal, and trichomonal infections - Abigail Norris Turner (2018)
BACKGROUND: Male circumcision (MC) decreases the risk of human immunodeficiency virus (HIV) acquisition in men. We explored associations between MC of the primary sex partner and women's risk of acquisition of chlamydial (Ct), gonococcal (GC), or trichomonal (Tv) infections. METHODS: We analyzed data from a prospective study on hormonal contraception and incident human immunodeficiency virus/sexually transmitted infection (STI) among women from Uganda, Zimbabwe, and Thailand. At enrollment and each follow-up visit, we collected endocervical swabs for polymerase chain reaction identification of Ct and GC; Tv was diagnosed by wet mount. Using Cox proportional hazards models, we compared time to STI acquisition for women according to their partner's MC status. RESULTS: Among 5925 women (2180 from Uganda, 2228 from Zimbabwe, and 1517 from Thailand), 18.6% reported a circumcised primary partner at baseline, 70.8% reported an uncircumcised partner, and 9.7% did not know their partner's circumcision status. During follow-up, 408, 305, and 362 participants had a first incident Ct, GC, or Tv infection, respectively. In multivariate analysis, after controlling for contraceptive method, age, age at coital debut, and country, the adjusted hazard ratio (HR) comparing women with circumcised partners with those with uncircumcised partners for Ct was 1.25 [95% confidence interval (CI) 0.96-1.63]; for GC, adjusted HR 0.99 (95% CI 0.74-1.31); for Tv, adjusted HR 1.05 (95% CI 0.80-1.36), and for the 3 STIs combined, adjusted HR 1.02 (95% CI 0.85-1.21). CONCLUSIONS: MC was not associated with women's risk of acquisition of Ct, GC, or Tv infection in this cohort. © 2008, American Sexually Transmitted Diseases Association.